Tax Planning and Firms’ Value in Nigeria - Sinebe, M. T.; Emudainohwo, O. B. (Research Parks Publishers, 2023)
The connection between tax preparation and firm’s value matters. Thus, this study examined tax planning proxy with income effective tax and cash effective tax influence on firm value proxy with Tobins Q in Nigeria. The researchers sampled forty-four non-financial firms listed on the Nigeria Exchange Group over the period 2011 to 2020. The variables data extracted from sampled firm’s annual report and account were subjected to panel multiple regressions analysis after rigorous data exploration. The study finds that income effective tax and cash effective tax has insignificant adverse impact on firm value for the period examined. The study recommends that, management should examine their tax savings activities to enable them to improve their firm’s value.